2019
DOI: 10.3390/ijms20040928
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Li4SiO4 Material for CO2 Capture: A Review

Abstract: Lithium silicate (Li4SiO4) material can be applied for CO2 capture in energy production processes, such as hydrogen plants, based on sorption-enhanced reforming and fossil fuel-fired power plants, which has attracted research interests of many researchers. However, CO2 absorption performance of Li4SiO4 material prepared by the traditional solid-state reaction method is unsatisfactory during the absorption/regeneration cycles. Improving CO2 absorption capacity and cyclic stability of Li4SiO4 material is a resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 82 publications
2
33
0
Order By: Relevance
“…2. Chemical looping separation of carbon dioxide [8,[15][16][17][18][19][20][21][22]. Chemical looping CO2 separation applies an (earth) alkali metal oxide (MO) as sorbent, to reversibly retain and set free CO2 (Figure 1b).…”
Section: Concept Of Chemical Loopingmentioning
confidence: 99%
“…2. Chemical looping separation of carbon dioxide [8,[15][16][17][18][19][20][21][22]. Chemical looping CO2 separation applies an (earth) alkali metal oxide (MO) as sorbent, to reversibly retain and set free CO2 (Figure 1b).…”
Section: Concept Of Chemical Loopingmentioning
confidence: 99%
“…Even though other metal oxides can react with CO 2 at high temperatures (Kyaw et al, 1996;Kato et al, 1999;Cot-Gores et al, 2012), the reactivity of Li 4 SiO 4 is relatively high. In our earlier research work, Li 4 SiO 4 was con rmed to have su cient performance as a TcES material at 700°C (Takasu et al, 2017(Takasu et al, , 2018 (Yan et al, 2019). For instance, Seggiani et al (2013) reported the sorption performance of Li 4 SiO 4 with di erent ratios (10-30 mass%) of K 2 CO 3 and Na 2 CO 3 , under 4% CO 2 concentration at 580°C and the sample with 30 mass% of K 2 CO 3 exhibited higher sorption capacity and durability than pure Li 4 SiO 4 (Yan et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…In our earlier research work, Li 4 SiO 4 was con rmed to have su cient performance as a TcES material at 700°C (Takasu et al, 2017(Takasu et al, , 2018 (Yan et al, 2019). For instance, Seggiani et al (2013) reported the sorption performance of Li 4 SiO 4 with di erent ratios (10-30 mass%) of K 2 CO 3 and Na 2 CO 3 , under 4% CO 2 concentration at 580°C and the sample with 30 mass% of K 2 CO 3 exhibited higher sorption capacity and durability than pure Li 4 SiO 4 (Yan et al, 2019). Yan et al (2019) also investigated the sorption performance of Li 4 SiO 4 , using a small mix (1-10 mass% and 5-20 mass%) of K 2 CO 3 and Na 2 CO 3 under 15% of CO 2 at 550°C.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To increase the useful energy of these system and decrease the operating costs, intermediate-temperature and high-temperature sorbents, including hydrotalcites [4], MgO-based sorbents [5], calcium oxides [6][7][8][9], and ceramic materials [10][11][12], have been examined as alternative sorbents because these materials can directly separate CO2 from hot flue gases in thermal power or sorption-enhanced steam methane reforming (SE-SMR) processes. Alkaline ceramic materials [13], especially lithium orthosilicate (Li4SiO4) [14,15], appear to be attractive sorbents because they have high theoretical CO2 capture capacities (36.7 wt.%), and a consistent recyclability.…”
Section: Introductionmentioning
confidence: 99%